Structural capital model for universities based on JDL data fusion model and information quality [Modelo de capital estructural para universidades basado en el modelo de fusión de datos JDL y la calidad de la información] (2020)
Intellectual capital is one of the most critical intangible active assets for universities, and there are multiple models to value it through the human, structural, and relational components. However, this is an open field of research that still demands new solutions to assess it effectively from each of its components. For the assessment of the structural component in higher education institutions, this study proposes a model that combines the assessment of the quality of information and the JDL data fusion model (joint directors of laboratories), which has been used in applications military. The proposed model is original in the methods used and their association, distributed in six levels that execute the pre-processing of the information, valuation of objects, valuation of the situation and the risk, and the refinement of the process. Besides, it evaluates the quality of the information, its traceability, and context to refine the process and obtain a more objective assessment taking into account the imperfection of the information for decision-making in the management of impact and risk. The model not only allows the assessment of structural capital, but also supports decision-making based on the quality of information and its impact. The functionality of the model is described by levels. © 2020, Associacao Iberica de Sistemas e Tecnologias de Informacao. All rights reserved.